Length weight relationship and condition factors of dusky sleeper (Eleotris fusca Forster, 1801) in the Cikaso River, Sukabumi - Faqih Baihaqi; Shafira Bilqis Annida; Alya Syafitri; Ufaira Suci Ramadhani; Nazwa Fairuz Nuraeni (Universitas Teuku Umar, 2026)
The Cikaso River is a flowing water ecosystem that stretches approximately 60 km in the southeastern part of Sukabumi Regency, West Java Province. This river is known to the local community as one of the main rivers with high fish biodiversity. One type of fish in these waters is the dusky sleeper (Eleotris fusca), locally known as the nyereh fish. The local community uses the nyereh fish as one of the fish for consumption. Until now, scientific studies on the biological aspects of nyereh fish, especially related to growth and condition factors, have been very limited. This study examines the relationship between length-weight and condition factor values of nyereh fish living in the Cikaso River, Sukabumi. Sample collection was executed throughout 2021, from January to December, using a trap fishing gear. A total of 513 individual fish were successfully collected with a total length ranging from 82 to 152 mm. The analysis of the relationship between total length and fish weight produced a regression equation W = 0.00001 L3.3233 with a coefficient of determination value of 0.9897. The slope value of the log curve of 3.3233 (b>3) indicates that the weight growth of the nyereh fish is more dominant than the growth of its length. Meanwhile, the fish condition factor values ranged from 0.86 to 1.26. The condition factor for nyereh fish reached its highest point at the start of the dry season in May and its lowest at the start of the rainy season in October